Aurangzeb : The Man and the Myth - Truschke, Audrey (Karachi Oxford University Press, 2017)
The field of South Asian History has been polarized and paralyzed by stereotypes of the Mughal Emperor Aurangzeb Alamgir (1658-1707).
Include Color Illustrations, Maps and Index
Keywords: Biography of Last Emperor Aurangzeb Alamgir